Secondary Metabolites in Drug Development: Tracing Their Historical and Therapeutic Impact - Anjna Kumari; Ruchi Sangal (Emerging Trends in Metabolites, 2024)
Secondary metabolites, also known as natural products, exhibit a level of structural and chemical diversity unmatched by synthetic small molecule libraries. These compounds, which have evolved to possess drug-like properties, continue to be a primary source for new medications and drug leads. Their discovery has significantly impacted advancements in chemistry, biology, and medicine, influencing drug development and therapeutic strategies throughout history. Derived from primary metabolic pathways such as photosynthesis, glycolysis, and the Krebs cycle, secondary metabolites are formed from the essential biosynthetic intermediates produced by these processes (Dewick, 2002). Plants and their extracts are composed of a diverse range of bioactive compounds or phytochemicals that vary in polarity. These phytochemicals form the basis for numerous pharmaceutical products. The specific components of a plant play a crucial role in identifying crude medicines, and they are typically associated with minimal adverse effects. Throughout history, humans have turned to nature, especially plants, in their search for new drugs. Consequently, many medicinal plants with therapeutic properties are now employed to treat various conditions. Historical records such as the Ebers Papyrus (circa 2900 B.C.) document approximately 700 plant-based remedies, such as gargles, pills, infusions, and ointments, which are listed in CITES Appendix II. Other ancient texts which provided extensive information on traditional medicinal plants, such as the Chinese Materia Medica with 52 formulas, the Shennong Herbal with 365 remedies, and the Tang Herbal with 850 drugs also detail the use of natural products. Given that only about 10% of global biodiversity has been explored for its potential biological activity, there remains a vast array of natural compounds yet to be discovered, highlighting the challenge of accessing this diverse chemical resource. Considering emerging diseases like cancers, AIDS, SARS, and bird flu, alongside growing environmental challenges, including biodiversity loss and land and water degradation, there is an urgent need to identify and isolate novel and beneficial molecules. These discoveries are crucial for addressing and mitigating various aspects of human health and environmental issues (Bacon and White, 2003).
Keywords: AIDS; Biodiversity; Medication; Natural product; SARS; photosynthesis; secondary metabolites